The Divide - Kay, Elizabeth (New York : Scholastic, 2007)
While hiking on the Continental Divide of Costa Rica, a young boy with a heart condition falls into a magical otherworld full of fantastical creatures.
"Chicken House."
First published: United Kingdom : The Chicken House, 2003.
5.1
5-8
5-8
Publisher's Weekly
Keywords: Heart -- Diseases -- Fiction; Costa Rica -- Fiction; Fantasy; Heart diseases -- Fiction; Costa Rica -- Fiction; Fantasy fiction; Adventure fiction